Evaluating the Validity of Dairy Calf Death Data and its Implications for Global Animal Welfare Initiatives - et al., Digvijay Singh (Revista Electronica de Veterinaria, 2024)
The dairy business is vital to the world's agriculture since it produces goods that are necessary for people to eat. But worries about the well-being of animals have grown in importance, especially in light of the death of dairy calves. The purpose of this research is to evaluate the reliability of dairy calf fatality data and investigate how it can affect international animal welfare schemes. The major drawback is the lack of agreement on the definition of perinatal mortality, which results in a range of figures. Of the 20 investigations, 10 clearly excluded abortion, while one broke out on the proportions of abortion and stillbirth. Interpretations are further complicated by differences in research designs as well as reporting timelines. While 12 researches were retrospective, it is difficult to ensure accuracy, particularly when included herds without information on perinatal death, seven investigations were prospective and allowed for better control over the quality of the data. Because of this aspect, retrospective studies might understate mortality. Even with an empty mean death statistic of 6.2%, significant methodological variances make caution necessary when examining nations or ways of farming. For comparisons between farms, regions, or nations to be valid, study methods must be carefully examined.